Prevention of accidents in project design in the BIM process: A bibliometric review - Azevedo, Vinícius Francis Braga de; Kohlman Rabbani, Emilia Rahnemay; Vasconcelos, Bianca M. (National Journal of City Management, 2024)
In recent decades, urban development has been marked by a growing search for solutions that promote the intelligence and sustainability of cities. In this context, the Prevention through Design (PtD) approach emerges as an important tool to enhance the safety and sustainable development of projects, from conception to deconstruction. This study aims to present a bibliometric analysis of academic productions on PtD that employ BIM, contributing to the advancement of knowledge in this field and the construction of safer, smarter, and more sustainable cities. Using the PRISMA methodology and the PICo approach, 37 articles were analyzed. The results highlight a significant increase in publications, particularly in 2022, led by China, followed by the USA. A probable future research trend is the use of PtD for subway stations. Journals such as Automation in Construction emerge as influential in this field. Co-authorship analysis indicates limited collaborations, while the citation network reveals the influence of journals like Automation in Construction and Safety Science. It is concluded that BIM for PtD represents an expanding research area with international relevance for the construction of safer and more efficient cities.
Keywords: Building Information Modeling; Occupational safety; Sustainable construction